RANCANG BANGUN PROTOTYPE SISTEM PERINGATAN DINI KENAIKAN AIR SUNGAI DAN POTENSI LONGSOR BERBASIS IOT - Restu Toriqiyatul Hayat; Andreas B Siahaan; Yosephus Ifanuel rumapea; Eka Dodi Suryanto; Dian Putra Saragi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to design and implement a prototype of an Internet of Things (IoT)-based early warning system for river water level rise and landslide potential. The system utilizes an ESP32 microcontroller as the main controller integrated with multiple environmental sensors, including an ultrasonic sensor for water level measurement, a soil moisture sensor, a vibration sensor, and a temperature and humidity sensor. The research method used is experimental, involving system design, hardware implementation, software development, and functional testing. The system is capable of monitoring environmental parameters in real-time and classifying conditions into three levels: safe, alert, and danger. The results show that the system successfully detects changes in environmental conditions and provides warnings through visual indicators, audio alarms, and IoT-based notifications. The multi-parameter approach improves the accuracy and reliability of the system in identifying potential flood and landslide risks. This prototype demonstrates effective performance and has the potential to be further developed into a real-world disaster mitigation system.